Prozaiczność relacji w triadzie szkolnej: uczeń – nauczyciel – rodzic - Ściupider-Młodkowska, Mirosława (Pedagogika Społeczna Nova, 2025)
Scientific Objective. Description and diagnosis of selected phenomena determining difficulties in relations in the school parent – student – teacher triad. Research problem and methods. What situations in the school triad reflect the arrhythmia and contradiction in relationships – the more communicators, the less authenticity, empathy and mutual understanding. The paradigm of constructivist thinking, interpretative analysis and critical discourse analysis were used. Process of argument. The school, as an institution, is increasingly experiencing disempowerment as a result of comprehensive access to knowledge, thus we observe a shaky security. It can be argued that school relationships involving pupils, teachers and parents alike are in crisis because they have adopted and implemented many forms of technological and virtually mediated contact, but they are mundane and insufficient for building trust.